THE POLITICAL ECONOMY OF PAKISTAN’S STRATEGIC POLICIES (Contemporary Journal of Social Science Review, 2025)
Pakistan's economic conditions, which determine its foreign policy alliances and security imperatives, greatly influence its strategic policymaking. This article critically explores the relationship between the State’s economic circumstances and its strategic policymaking by evaluating how international financial institutions (IFIs) and global alliances have shaped Pakistan's economic and national security policies relatively. Pakistan's capacity to make independent strategic decisions is constrained by its economic shortcomings, specifically those marked by budget deficits, debt dependence, and reliance on foreign funding. Defence financing and entire financial oversight are significantly affected by economic restructuring programs, budget cuts, and policy constraints, most of the time, that have been a consequence of financial institutions like the World Bank and the International Monetary Fund (IMF) policies. Due to this, Pakistan's diplomatic mobility is affected by a specific set of patterns of reliance on international associations. These connections often function as diplomatic restrictions and monetary essentials relatively. This research paper will highlight how Pakistan’s ongoing economic instability leads to reflexive strategic decisions, frequently valuing compact financial relief over a country's sustainability. Relying too much on financial institutions and economic partnerships with other countries can weaken a nation's independence and decision-making power, even though engaging in global trade and finance is essential. Pakistan can enhance its economic growth and decision-making by adopting a balanced approach to diversifying regional trade, handling debt wisely, and increasing domestic revenue. Finding the right direction between financial stability and strategic flexibility is crucial to maintaining national security and steady growth.